2013
DOI: 10.1016/j.cryogenics.2013.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Advances in development of quartz crystal oscillators at liquid helium temperatures

Abstract: This work presents some recent results in the field of liquid helium bulk acoustic wave oscillators. The discussion covers the whole development procedure starting from component selection and characterization and concluding with actual phase noise measurements. The associated problems and limitations are discussed. The unique features of obtained phase noise power spectral densities are explained with a proposed extension of the Leeson effect.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…5) than the components from lower-resistive inks (DP1931 -blue line). This observation is in agreement with the data presented in [19] for SMD 0805 thick-film resistors from YA-GEO. The temperature dependence of normalized Rr(T) = R(T)/R 0 ( Fig.…”
Section: Data Collectingsupporting
confidence: 82%
“…5) than the components from lower-resistive inks (DP1931 -blue line). This observation is in agreement with the data presented in [19] for SMD 0805 thick-film resistors from YA-GEO. The temperature dependence of normalized Rr(T) = R(T)/R 0 ( Fig.…”
Section: Data Collectingsupporting
confidence: 82%
“…Interestingly, it is no longer the deficiency of the Q-factor, which halts further progress in the reduction of phase fluctuations, but rather the intrinsic fluctuations of the BAW resonator itself [9,10]. In particular, it has been concluded that further improvement of BAW based frequency sources could only be achieved by reducing the resonator flicker phase self-noise, since this is the dominant noise source of ultra-stable BAW oscillators both at cryogenic and room temperature [9,11].…”
mentioning
confidence: 99%
“…Interestingly, it is no longer the deficiency of the Q-factor, which halts further progress in the reduction of phase fluctuations, but rather the intrinsic fluctuations of the BAW resonator itself [9,10]. In particular, it has been concluded that further improvement of BAW based frequency sources could only be achieved by reducing the resonator flicker phase self-noise, since this is the dominant noise source of ultra-stable BAW oscillators both at cryogenic and room temperature [9,11].The origin of the flicker frequency noise is still poorly understood despite its significant influence on many systems [12,13] ranging from biological substances[14] to superconducting electronics [15,16]. The influence on the frequency stability of high-performance quartz oscillators on time scales of order 1-10 seconds is welldocumented [10,17,18] with several attempts to understand its origins [19][20][21].…”
mentioning
confidence: 99%
“…The piezoelectricity and high acoustic Q-factor ensures significant "self" transductance of the BAW resonator with high electromechanical sensitivity without the necessity of an externally added transducer. These devices were originally developed for high stability frequency applications [37][38][39] and more recently adapted at low temperatures for quantum information applications [32,34,40] and fundamental physics tests [33]. Indeed it seems like the quantum limited read out of these devices in the quantum ground state will soon be achieved.…”
Section: Introductionmentioning
confidence: 99%